Quantitative and statistical research methods : from hypothesis to results - Martin, William E. 1948-; Bridgmon, Krista D., 1979- (Jossey-Bass, 2012)
"Quantitative and Statistical Research Methods offers a guide for psychology, counseling, and education students in the use of statistics and research designs, combined with guidance on using SPSS in the course of their research. Each chapter covers a research problem, taking the student through identifying research questions and hypotheses; identifying, classifying, and operationally defining the study variables; choosing appropriate research designs; conducting power analysis; choosing an appropriate statistic for the problem; using a data set; conducting data screening and analyses (SPSS); interpreting the statistics; and writing the results related to the problem. Designed so students will know how to plan research and conduct statistical analyses using several different procedures"--Resumé vydavatele
Keywords: společenské vědy -- metodologie; sociální výzkum -- metodologie; kvantitativní výzkum; statistické metody; SPSS (software); social sciences -- methodology; social research -- methodology; quantitative research; statistical methods; učebnice; textbooks